2000
DOI: 10.1111/j.1348-0421.2000.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Post‐Translational Modification of Actinobacillus actinomycetemcomitans Fimbrillin

Abstract: Fresh isolates of Actinobacillus actinomycetemcomitans produce bundle-forming fimbriae. The exact molecular mass of A. actinomycetemcomitans fimbrillin, a structural subunit of fimbriae, was determined by liquid chromatography-electrospray ionization mass spectrometry. Three major molecular species with 6,226.0, 6,366.0, and 6,513.0 Da were detected in a purified fimbrial fraction from the strain 310-a. These molecular masses were significantly higher than the molecular weight (5,118 Da) calculated from nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
2
24
1
Order By: Relevance
“…The involvement of glycoconjugates in the adherence of A. actinomycetemcomitans to surfaces was also suggested by Fine et al (3). With regard to this, we previously proposed the possibility that the fimbriae of A. actinomycetemcomitans are glycosylated (8). However, the present result suggests that surface-exposed carbohydrate residues other than fimbriae-associated residues are involved in the biofilm formation.…”
Section: Disorganization Of 310-df Biofilm With Sodium Metaperiodate contrasting
confidence: 55%
See 1 more Smart Citation
“…The involvement of glycoconjugates in the adherence of A. actinomycetemcomitans to surfaces was also suggested by Fine et al (3). With regard to this, we previously proposed the possibility that the fimbriae of A. actinomycetemcomitans are glycosylated (8). However, the present result suggests that surface-exposed carbohydrate residues other than fimbriae-associated residues are involved in the biofilm formation.…”
Section: Disorganization Of 310-df Biofilm With Sodium Metaperiodate contrasting
confidence: 55%
“…The fimbriae are composed of subunits of approximately 6.5 kDa (7), which are post-translationally modified (8), and share amino acid sequence similarity with type IV pilin of gram-negative bacteria (7,12). Recent genetic and molecular biological studies have revealed that the flp-rcp-tad gene cluster is required for fimbriae production (5,7,11).…”
mentioning
confidence: 99%
“…This pilus is encoded by a cluster of 14 chromosomal genes (13), the first of which, flp-1, encodes the major pilin subunit (14). A. actinomycetemcomitans Flp-1 protein been shown to be posttranslationally modified, probably by glycosylation (11). It is possible that this posttranslational glycosylation includes an N-acetylglucosamine component and that cleavage of this sugar by DspB alters the adhesive properties of the pili, thereby releasing cells from the aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…The glycan was proven to be crucial for collagen binding and the protection of EmaA against proteolytic degradation (439). Previously, the potential glycosylation of the Flp fimbriae was reported (440).…”
Section: Protein Glycosylationmentioning
confidence: 99%